Urban Growth and its Impact on Tangail Municipal Area - Sarker, BC; Shutradhar, SC; Khan, A; Saifullah, ASM; Ruma, AB (Journal of Environmental Science and Natural Resources, 2016)
The study has endeavored to investigate the urban development and its impacts on Tangail municipality, Tangail, Bangladesh. The factual data have been collected from secondary sources, while the perceptual data are based on survey questionnaires on the opinions of respondents. Data were collected through instant spot observation (transect survey) and in-depth consultation, and interviews. The study displays that, the population of Tangail municipality rapidly augmented after 1971. For instance, the population rose from 19.875 thousand in 1961 to 128.785 thousand in 2001. Additionally, the area of Tangail municipality was 15.50 km2 in 1981 which has expanded to 29.40 km2 in 2001. The proposed area of Tangail municipality was five km2. In 1951 the level of urbanization in Tangail municipality was 1.79% which has experienced a sharp rise of 12.99 % in 2001. The study found that, the enlarged urbanization in Tangail town has resulted in higher population density, increased demand for food, alleviation of environmental pollution, increased traffic congestion, generation of solid waste, inadequate garbage disposal, effluent disposal into rivers, crime, and disappearing green and open space in the Tangail municipality. J. Environ. Sci. & Natural Resources, 8(2): 163-166 2015